2021
DOI: 10.1016/j.cjca.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Actigraphy (Wearable Digital Sensors to Monitor Activity) in Heart Failure Randomized Clinical Trials: A Scoping Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
(84 reference statements)
2
6
0
Order By: Relevance
“…While they recommend the use of actigraphy outcomes to assess treatment effects in clinical trials in patient populations with limited activity, they found substantial heterogeneity in the use and methodology employed. Similar findings have also been reported more recently in the context of clinical trials in heart failure, 6 Huntington's disease ,7 and in Parkinson's disease. 8 The idea of developing actigraphy endpoints imitates what is usually done with health outcomes, where a clinical assessment is performed to collect data on a specific endpoint (continuous, categorical, etc.)…”
Section: Introductionsupporting
confidence: 86%
“…While they recommend the use of actigraphy outcomes to assess treatment effects in clinical trials in patient populations with limited activity, they found substantial heterogeneity in the use and methodology employed. Similar findings have also been reported more recently in the context of clinical trials in heart failure, 6 Huntington's disease ,7 and in Parkinson's disease. 8 The idea of developing actigraphy endpoints imitates what is usually done with health outcomes, where a clinical assessment is performed to collect data on a specific endpoint (continuous, categorical, etc.)…”
Section: Introductionsupporting
confidence: 86%
“…19 Also, regarding results, it's well known from the literature that functional capacity mostly correlates positively with sleep outcomes. 8 9 10 However, in this case, we have noticed that the functional capacity improved dramatically on doing the combined aerobic and resistance training for 8 weeks, however, his sleep outcomes deteriorated. Therefore, unexpectedly, there is no association/correlation between functional capacity and sleep outcomes.…”
Section: Discussionmentioning
confidence: 75%
“…As a result, future research may evaluate whether the extended TRS‐HF DM with the addition of NT‐proBNP can prognosticate more sensitive HF outcomes. These may include changes in accelerometry data as a proxy for mobility, or expanded HF outcomes that, for example, include the initiation of loop diuretics 35,36 . Furthermore, understanding whether the extended TRS‐HF DM can improve outcomes or identify people who may derive increased benefit from SGLT2 inhibition may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…These may include changes in accelerometry data as a proxy for mobility, or expanded HF outcomes that, for example, include the initiation of loop diuretics. 35,36 Furthermore, understanding whether the extended TRS-HF DM can improve outcomes or identify people who may derive increased benefit from SGLT2 inhibition may be warranted. Validation of the TRS-HF DM and the TIMI Biomarker Score for Heart Failure in Diabetes could also be explored in lower-risk populations and individuals with recent ACS to establish further the prognostic and clinical utility.…”
Section: Discussionmentioning
confidence: 99%